Axial compressive performance of steel tube columns filled with steel fiber-reinforced high strength concrete containing tire aggregate after exposure to high temperatures. (15th September 2020) - Karimi, Amirhossein; Nematzadeh, Mahdi
Highlights: Post-heating performance of CFST columns containing tire aggregate and steel fiber was studied. A relationship for predicting the loading capacity of CFST columns under heat was proposed. Including scrap-tire aggregate in concrete mixture lowered the strength of confined specimens. Thermal treatment had no particular increasing effect on the decline of strength caused by the presence of tire. Abstract: The performance of concrete-filled steel tube (CFST) columns including scrap-tire rubber under compression and in particular changes in their behavior after thermal treatment has remained mostly understudied. This has led to the lack of the use of rubberized concrete in these columns. This study attempted to examine the post-heating performance of CFST columns subject to several temperatures (20, 250, 500, and 750 °C) with regard to the amount of scrap-tire rubber aggregate used as a volume fraction of sand (0, 5, and 10%), quantity of steel fibers in volume (0, 1, and 1.5%), and the ratio of the outer diameter to thickness of the steel tube (43 and 25.4). The specimens had high-strength concrete cores and seamless steel tubes. The total number of manufactured confined and unconfined cylindrical specimens was 114, which were then exposed to heat and axial compressive testing. Through these tests, the loading capacity, ductility, toughness, and compressive load-strain curves of different specimens were explored. Based on the results, although including the scrap-tire aggregate (by 10%) in the concrete mixture lowered the strength of the confined specimens (by 12%), thermal treatment had no particular increasing effect on this decline. Furthermore, as the quantity of steel fibers and the thickness of the steel tube in the heated and non-heated CFST specimens increased, toughness increased in all the specimens, and the ductility had an ascending trend in most specimens. In addition, the optimum quantity of steel fibers used here was 1%. In this regard, although the fibers affected the compressive strength of the CFST specimens negligibly, they demonstrated a considerable improving effect on the ductility and absorbed energy in all specimens particularly the heated ones. Up to 250 °C, the decline in strength was negligible, while above this temperature, this decline in strength was much more considerable, and also, the post-peak slope of all the curves decreased. Finally, due to the importance of predicting the strength of CFST columns after exposure to heat, a relationship for predicting the loading capacity of these columns under heat was proposed and the associated results were compared with the experimental results of this work as well as the experimental results reported by others. Good consistency was seen between the predicted and experimental results.